Improved long term cycling of polyazulene/reduced graphene oxide composites fabricated in a choline based ionic liquid - Suominen Milla; Damlin Pia; Granroth Sari; Kvarnström Carita (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
To improve the energy density of supercapacitors, novel electronically conducting polymers should be introduced to the research field. Polyazulene is a well-suitable candidate as it exhibits good capacitive behavior both in organic solvents as well as in various ionic liquids, but especially its long term cycling stability should be improved. Previously, enhanced properties have been obtained by combining conducting polymers with carbon nanomaterials to fabricate composites. This work presents an ionic liquid assisted electrochemical polymerization and characterization of polyazulene-reduced graphene oxide composites. The ionic liquid of our choice is choline-based liquid salt. We prepared stable dispersions of graphene oxide in this ionic liquid and performed potentiodynamic electropolymerization of azulene in the mixture. Changing the concentration of graphene oxide between 0.1 and 2 mg mL(-1) had no remarkable effect on the polymerization or electrochemical behavior of the composite materials. The composites exhibit higher capacitances compared to neat polymer films determined by cyclic voltammetry and electrochemical impedance spectroscopy. The obtained films also exhibit excellent cycling stabilities retaining over 90% of their initial capacitance with tendency towards improved cycling stability when combined with reduced graphene oxide. The successful incorporation and reduction of graphene oxide was determined by several spectroscopic techniques.